Correlation between Organizational Memory and Innovative Work Behavior - Etikariena, Arum; Muluk, Hamdi (Makara Human Behavior Studies in Asia, 2014)
This study aims to determine the relationship between organizational memory and innovative work behavior. The study was conducted on 100 employees from various levels and positions in a company that produce and trade electronic solar equipment. To measure the organizational memory, we used Organizational Memory Scale developed by Dunhamm (2010) with ?=0.75. Then, to measure innovative work behavior, we used Innovative Work Behavior Scale from Janssen (2000) with ?=0.80. The results show that there is positive and significant correlation between organizational memory and innovative workbehavior (r=0.35; p<0.01). Hierarchical-regression analysis shows that (1) altogether education level, job type and organizational memory influences 19% of variance in innovative behavior; (2) when these variables are analysed together, only education level shows significant impact on innovative behavior. We discuss theoretical and methodological reasons for these results and offer future direction for research.